Estrogen Receptor β in Melanoma: From Molecular Insights to Potential Clinical Utility - Marzagalli, Monica; Montagnani Marelli, Marina; Casati, Lavinia; Fontana, Fabrizio; Moretti, Roberta Manuela; Limonta, Patrizia (Frontiers in Endocrinology, 2016)
Cutaneous melanoma is an aggressive tumor with its incidence increasing faster than any other cancer in the past decades. Melanoma is a heterogeneous tumor, with most patients harboring mutations in the BRAF or NRAS oncogenes, leading to the overactivation of the MAPK/ERK and PI3K/Akt pathways. The current therapeutic approaches are based on therapies targeting mutated BRAF and the downstream pathway, and on monoclonal antibodies against the immune checkpoint blockade. However, treatment resistance and side effects are common events of these therapeutic strategies. Increasing evidence supports that melanoma is a hormone-related cancer. Melanoma incidence is higher in males than in females and females have a significant survival advantage over men. Estrogens exert their effects through estrogen receptors (ER and ERβ) that exert opposite effects on cancer growth: ER is associated with a proliferative action and ERβ with an anticancer effect. ERβ is the predominant estrogen receptor in melanoma and its expression decreases in melanoma progression, supporting its role as a tumor suppressor. Thus, ERβ is now considered as an effective molecular target for melanoma treatment. 17β-estradiol was reported to inhibit melanoma cells proliferation. However, clinical trials did not provide the expected survival benefits. In vitro studies demonstrate that ERβ ligands inhibit the proliferation of melanoma cells harboring the NRAS (but not the BRAF) mutation, suggesting that ERβ activation might impair melanoma development through the inhibition of the PI3K/Akt pathway. These data suggest that ERβ agonists might be considered as an effective treatment strategy, in combination with MAPK inhibitors, for NRAS mutant melanomas. In an era of personalized medicine, pretreatment evaluation of the expression of ER isoforms together with the concurrent oncogenic mutations should be considered before selecting the most appropriate therapeutic intervention. Natural compounds that specifically bind ERβ have been identified. These phytoestrogens decrease the proliferation of melanoma cells. Importantly, these effects are unrelated to the oncogenic mutations of melanomas, suggesting that, in addition to their ERβ activating function, these compounds might impair melanoma development through additional mechanisms. A better identification of the role of ERβ in melanoma development will help increase the therapeutic options for this aggressive pathology.